The Acute Effects of Upper Extremity Stretching on Throwing Velocity in Baseball Throwers. (7th November 2013) - Williams, Michael; Harveson, Lanisa; Melton, Jason; Delobel, Ashley; Puentedura, Emilio J.
Abstract : Purpose . To examine the effects of static and proprioceptive neuromuscular facilitation (PNF) stretching of the shoulder internal rotators on throwing velocity. Subjects . 27 male throwers (mean age = 25.1 years old, SD = 2.4) with adequate knowledge of demonstrable throwing mechanics. Study Design . Randomized crossover trial with repeated measures. Methods . Subjects warmed up, threw 10 pitches at their maximum velocity, were randomly assigned to 1 of 3 stretching protocols (static, PNF, or no stretch), and then repeated their 10 pitches. Velocities were recorded after each pitch and average and peak velocities were recorded after each session. Results . Data were analyzed using a3 × 2 repeated measures ANOVA. No significant interaction between stretching and throwing velocity was observed. Main effects for time were not statistically significant. Main effects for the stretching groups were statistically significant. Discussion . Results suggest that stretching of the shoulder internal rotators did not significantly affect throwing velocity immediately after stretching. This may be due to the complexity of the throwing task. Conclusions . Stretching may be included in a thrower's warm-up without any effects on throwing velocity. Further research should be performed using a population with more throwing experience and skill.